A szelf megerősítése terápiás írással. A fikció, mint eszköz - MIKOLA NYÍRI, Emese (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Strengthening the Self with Therapeutic Writing. Fiction as a Tool. In therapy, we can integrate in our work things that did not happen actually. This is also valid in the case of writing therapy. When a patient accepts a fictional practice, and tries to perform it, it breaks down his own self-defense mechanism more easily. Such a fictional practice could be talking with a body part or bad trait, rewriting the story of a trauma, introducing new characters, or telling the story from a different perspective. A world that does not follow the rules of reality can give an internal liberation that strengthens the self, weakened by external conditions, and heals the damaged self. That is what Celia Hunt’s book, Therapeutic Dimension of Autobiography in Creative Writing, is about, and Thompson Kate in her The Therapeutic Journal Writing. An Introduction for Professionals and James W. Pennebaker and John F. Evans in their Expressive Writing: Words That Heal also devote several chapters specifically to this topic. The most important criteria in this type of writing are to be truly authentic without any role-play. The wisdom of trauma lies in not identifying with the circumstances that make our life narrow and turning to the whole world. This is analogous to religious conversion, the search for the Kingdom of God, the childish open-minded view of the world that Jesus encouraged us to have.